Prevalence and transmission patterns of Mycoplasma bovis in comingled Holstein dairy heifers from two different parent farms - Billy I. Smith; Larry K. Fox; Helen W. Aceto (BMC Veterinary Research)
Abstract Background Mycoplasma bovis probably enters dairy herds when carrier animals are introduced. Comingled calves that become subclinical M. bovis carriers could promote cross-dairy transmission. A prospective cohort study in Holstein heifers from two unrelated herds (Farms A and B previously M. bovis positive and negative, respectively) comingled at a facility raising only their calves assessed: 1). prevalence of asymptomatic M. bovis infection; 2). associations between four anatomic sites (nares, eyes, ear canal, vagina; M. bovis culture with PCR confirmation). Fifteen calves per farm were enrolled every 4 months. Swabbing solutions were first collected at parent farms, thereafter monthly for 6 months, then quarterly to 21 months. Results Three heifers from each dairy were lost after enrollment leaving 144 heifers (72 per farm) in the analysis. On day 1, a Farm A calf vaginal sample was the single M. bovis positive. While comingled, positives increased dramatically. Days of age to first positive were not different between farms (Farm A median = 109, range 42–561 days; Farm B median = 110, range 33–404 days; P = 0.96). Overall, 125/144 heifers yielded 634 positive samples, intranasal (46.7%), ocular (25.7%), vaginal (17.8%), ear canal (9.8%). The most common combinations were eye/nose (55/634, 43.3%) and nose/vagina (21/634, 16.5%). Intranasal positives increased exponentially at 2–3 months of age, plateauing over 4–10 months, and were more frequent than non-nose (Incidence Rate Ratio 1.44, 95% CI 1.41–1.47; P < 0.001). Positive combinations involving the nose temporally lagged the intranasal alone positives, but eventually reached similar frequencies. After returning to the parent farms, frequency of intranasal positives declined more rapidly than did non-nose. Conclusions M. bovis was cultured from all sites, but the nose appears most critical for transmission. Once intranasal carriage escalated, virtually all calves were subsequently positive at least once at one or more sites, indicating how readily asymptomatic M. bovis can disseminate in a population of animals and potentially manifest as clinical disease later in life.